Urgensi Pencatatan Perkawinan Perspektif Maslahah Sa’id Ramadhan Al Bouty : (Studi Kasus Di Kecamatan Pakusari, Kabupaten Jember Jawa Timur) - Awaliya Safithri (Universitas Sains dan Teknologi Komputer, 2019)
Marriage registration is very important because it has implications for the rights and obligations of married couples and there is legal protection if a problem occurs. Couples who enter into a marriage without registration are called the practice of siri marriage, a marriage which takes place with the presence of two witnesses and a guardian as well as a marriage agreement, but is not registered at the KUA. This research aims to determine the urgency of registering marriages and the reasons why people carry out unregistered marriages and the causes and effects that occur to wives and children from unregistered marriages as well as the urgency of registering marriages from the perspective of maslahah Sa'id Ramadhan Al Bouthy. The method used in this research uses qualitative methods, namely research that produces descriptive data in the form of speech or writing and behavior that can be observed from the people (subjects) themselves. The results of this research show that there are several factors in the occurrence of unregistered marriages, namely: educational factors, economic factors, and environmental factors. Meanwhile, the urgency of registering marriages according to Sa'id Ramadhan Al Bouthy is